Response of Soil Moisture to Typical Rainfall at Different Stands and Slope Sites in Qiaoshan Forest Region - GUO Yixuan; LI Jing; XU Guoce; ZHANG Yixin; CHEN Xi; GU Fengyou; WANG Bin (Shuitu Baochi Xuebao)
[Objective] Rainfall is the main source of soil water supply, which directly affects the distribution characteristics of soil water, and then affects the growth of vegetation, to explore the response of soil moisture to typical rainfall at different stands and slope sites in Qiaoshan forest region. [Methods] The Qiaoshan forest area on the southern Loess Plateau was taken as the research object. Through monitoring the rainfall and soil moisture at different depths of typical stands (broad-leaved pure forest and mixed forest), the response characteristics of soil moisture at different layers to rainfall patterns under different vegetation cover and slope location conditions were explored. [Results] 1) Rainfall during the study period was mainly concentrated in August, September and October, with the highest rainfall being 251.7 mm in September. The seasonal differences in soil moisture in the same soil layer at different points were significant (p≤0.05), and the average soil moisture in all soil layers was the lowest in summer.2) During moderate rainfall events, only shallow soil moisture content responded to rainfall, and the response intensity of soil moisture content to rainfall in mixed forest was greater than that in broad-leaved pure forest.3) In the event of heavy rain, the response of soil moisture to rainfall was greater in the mixed forest than in the pure broad-leaved forest, and the response relationship was as follows: lower slope > middle slope > upper slope for the shallow layer, and upper slope > middle slope > lower slope for the deep layer.4) In the event of heavy rainfall, the response of soil moisture to rainfall was greater in broad-leaved pure forest than in mixed broad-leaved forest, and the response relationship was as follows: lower slope > middle slope > upper slope for the shallow layer, and upper slope > middle slope > lower slope in the deep layer.5) In the three rainfall events, the supplement amount of the mixed forest was 1.55, 1.65 and 1.00 times that of the pure broad-leaved forest, respectively. [Conclusion] It is of great significance to study the response of soil moisture to rainfall and the process of shallow soil moisture movement in Qiaoshan forest area for optimal allocation of rainfall resources and sustainable restoration of forest ecosystems.